An innovative method for occluding the urethral meatus and accessing urethra strictures in retrograde urethrography in males - Wei Li; Libo Man; Guanglin Huang (BMC Urology, 2023)
Abstract Objectives To observe and evaluate the effectiveness and safety of using a sponge plug method to occlude the urethral meatus during retrograde urethrography (RUG) for accessing male urethral strictures. Methods 40 male patients with a mean age of 51.4 years and a history of urethral injury were primarily diagnosed with urethral stricture using a urethrocystoscope. RUG was performed using a ureteral catheter with a sponge plug inserted into the external meatus. Iodixanol, a contrast medium, was injected into the urethra or bladder for performing RUG and voiding cystourethrography (VCUG). The patients were positioned obliquely to obtain urethrograms. Results All X-ray radiologic procedures for performing urethrography were successful without any overflow of contrast liquid observed. In all cases, the sponge plugs became visible in the resulting images. The external meatuses were directly visualized in all cases on the obtained images, allowing identification of the number, location, and length of strictures as well as coexistent pathologies such as fistulas. In one case, the plug slipped off the meatus immediately after completing the procedure. The pain Visual Analogue Scale (VAS) was 0 to 2, mean 0.35. No instances of complication or adverse reactions was observed. Conclusions The sponge plug effectively occludes the external urethral meatus for retrograde urethrography, enabling visualization of the actual caliber of the entire urethra, including the strictures and external meatus, by filling it with contrast liquid. This technique is safe and well-tolerated by patients.